2013
DOI: 10.1638/2012-0273r.1
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE, PREVALENCE AND INTENSITY OF INTERNAL PARASITE INFECTIONS OF AFRICAN LIONS (PANTHERA LEO) IN ENCLOSURES AT A RECREATION PARK IN ZIMBABWE

Abstract: A coprological survey was conducted to determine the types, prevalence, and intensity of infection of internal parasites in a population of captive African lions (Panthera leo) at a recreational game park in Zimbabwe. Individual fecal samples were collected on three occasions over a 4-month period from each of 30 lions (55%) out of 55 animals held. The samples were examined using flotation and sedimentation techniques to assess the presence and count of parasite eggs, oocysts, and cysts per gram of feces as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…in non-human primates were reported to be more prevalent [10] [15] [19] [36]. The incidence of Toxocara cati and Toxascaris leonine in Lions in the current study was supported by Okulewicz et al [37], Pawar et al [38], Mukarati et al, [39]. In line with the present study Engh et al [40] reported that Toxocara canis was infecting hyena in the Masai Mara national reserve of Kenya while Luty [41] recovered it in the feces of foxes in the University zoological garden of south western Nigeria.…”
Section: Identification Of Species Of Gastrointestinal Parasitessupporting
confidence: 69%
“…in non-human primates were reported to be more prevalent [10] [15] [19] [36]. The incidence of Toxocara cati and Toxascaris leonine in Lions in the current study was supported by Okulewicz et al [37], Pawar et al [38], Mukarati et al, [39]. In line with the present study Engh et al [40] reported that Toxocara canis was infecting hyena in the Masai Mara national reserve of Kenya while Luty [41] recovered it in the feces of foxes in the University zoological garden of south western Nigeria.…”
Section: Identification Of Species Of Gastrointestinal Parasitessupporting
confidence: 69%
“…Wildlife farms (herein referred to as facilities that breed non-domesticated species for commercial purposes) in particular can create opportunity for pathogen transmission between wild animals and their human caretakers because of regular or prolonged contact for husbandry purposes [13]. Furthermore, conditions often associated with wildlife farms, such as high concentrations of wild animals in the same enclosures, poor hygiene, and stress associated with captive conditions, can reduce resistance to pathogens and increase the risk for transmission of disease [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…in captive mammals at the zoo of Zagreb, Croatia, the parasite was detected in 38 of the 131 animals (29%) tested using epifluorescence microscopy, and positive PCR results were obtained for 23 of 27 (85%) samples [37]. Results concerning the presence of Giardia in nonhuman primates housed in two Spanish zoological gardens showed an infection rate of 60% (12/20) by microscopy, versus 70% (14/20) by PCR [38]. Mukarati et al also found that the prevalence of Giardia spp.…”
Section: Discussionmentioning
confidence: 98%